Conditions: F1-F2 F1: No directed edge name can appear more than once as these φ can not be plugged together: φ ˆ a ψ ˆ = a ψ
Conditions: F1-F2 F1: No directed edge name can appear more than once as these φ can not be plugged together: φ ˆ a ψ ˆ = a ψ F2: No box can appear more than once to prevent overlap (which B � A � B � � A . . . . . . we do not allow in this formalism): �� = A A . . . . . .
Conditions: F1-F2 F1: No directed edge name can appear more than once as these φ can not be plugged together: φ ˆ a ψ ˆ = a ψ F2: No box can appear more than once to prevent overlap (which B � A � B � � A . . . . . . we do not allow in this formalism): �� = A A . . . . . .
Conditions: C1-C3 C1: An edge entering a !-box can’t be on a node already in that B � B !-Box: � B φ φ [ˆ = a � B a
Conditions: C1-C3 C1: An edge entering a !-box can’t be on a node already in that B � B !-Box: � B φ φ [ˆ = a � B a
Conditions: C1-C3 C1: An edge entering a !-box can’t be on a node already in that B � B !-Box: � B φ φ [ˆ = a � B a C2: Nested !-Boxes around an edge must be nested in the same way B A � A in the rest of the tensor: � A φ ψ φ [[ˆ ψ = a � A � B a
Conditions: C1-C3 C1: An edge entering a !-box can’t be on a node already in that B � B !-Box: � B φ φ [ˆ = a � B a C2: Nested !-Boxes around an edge must be nested in the same way B A � A in the rest of the tensor: � A φ ψ φ [[ˆ ψ = a � A � B a
Conditions: C1-C3 C1: An edge entering a !-box can’t be on a node already in that B � B !-Box: � B φ φ [ˆ = a � B a C2: Nested !-Boxes around an edge must be nested in the same way B A � A in the rest of the tensor: � A φ ψ φ [[ˆ ψ = a � A � B a C3: Bound edges must be in compatible !-boxes: B = φ [ˆ a � B ψ ˇ φ a a ψ a
Conditions: C1-C3 C1: An edge entering a !-box can’t be on a node already in that B � B !-Box: � B φ φ [ˆ = a � B a C2: Nested !-Boxes around an edge must be nested in the same way B A � A in the rest of the tensor: � A φ ψ φ [[ˆ ψ = a � A � B a C3: Bound edges must be in compatible !-boxes: B = φ [ˆ a � B ψ ˇ φ a a ψ a
Operations The operation Kill removes a !-box and all nodes and edges in it:
Operations The operation Kill removes a !-box and all nodes and edges in it: � B �→ 1 , [ e � B �→ ǫ, � e ] B �→ ǫ ] � Kill B := [ G
Operations The operation Kill removes a !-box and all nodes and edges in it: � B �→ 1 , [ e � B �→ ǫ, � e ] B �→ ǫ ] � Kill B := [ G Expanding a !-box creates a new copy of its contents with new names for all new edges/boxes. Write fr ( G ) for G with all names replaced by new ones (choosen by predetermined function fr ).
Operations The operation Kill removes a !-box and all nodes and edges in it: � B �→ 1 , [ e � B �→ ǫ, � e ] B �→ ǫ ] � Kill B := [ G Expanding a !-box creates a new copy of its contents with new names for all new edges/boxes. Write fr ( G ) for G with all names replaced by new ones (choosen by predetermined function fr ). � B �→ � B fr ( G ) , [ e � B �→ [ e � B fr ( e ) , � e ] B �→ � � Exp B := [ G G fr ( e ) � e ] B ]
Table of Contents Introduction Tensor notation Definitions Induction Summary
Spider Node Definition := :=
Spider Node Definition := := Theorem = A A B B
Spider Node Definition := := Theorem = A A B B We would like to do induction on !-box B splitting into a base case (after Kill B ) and an inductive step (proving Exp B from original).
Induction Kill B ( G = H ) ( G = H ) = ⇒ Exp B ( G = H ) (Induction) G = H
Induction Kill B ( G = H ) Fix B ( G = H ) = ⇒ Exp B ( G = H ) (Induction) G = H
Spider Theorem ( Kill B ) Theorem (base) = A A
Spider Theorem ( Kill B ) Theorem (base) = A A Proof. = A A
Spider Theorem ( Kill B ) Theorem (base) = A A Proof. = = A A A
Spider Theorem ( Fix B = ⇒ Exp B ) Theorem ⇒ (step) = = A A A B B A B B
Spider Theorem ( Fix B = ⇒ Exp B ) Theorem ⇒ (step) = = A A A B B A B B Proof. A B
Spider Theorem ( Fix B = ⇒ Exp B ) Theorem ⇒ (step) = = A A A B B A B B Proof. = A A B B
Spider Theorem ( Fix B = ⇒ Exp B ) Theorem ⇒ (step) = = A A A B B A B B Proof. = = A A B B A B
Spider Theorem ( Fix B = ⇒ Exp B ) Theorem ⇒ (step) = = A A A B B A B B Proof. = = = A A A B B A B B
Spider Theorem ( Fix B = ⇒ Exp B ) Theorem ⇒ (step) = = A A A B B A B B Proof. IH = = = = = A A A A B B B A B B
Spider Theorem ( Fix B = ⇒ Exp B ) Theorem ⇒ (step) = = A A A B B A B B Proof. IH = = = = = A A A A A B B B B A B B
Recommend
More recommend